Boardroom dancing : transformation stories from corporate activist - Fakude, Nolitha (Johannesburg : Pan Macmillian South Africa, 2019)
"Nolitha grew up as a shopkeeper's daughter in the Eastern Cape, studied at the University of Fort Hare and then entered the workplace in 1990 as a graduate trainee at Woolworths. Subsequently, she has worked in very senior positions at some major blue-chip companies, including Woolworths, Nedbank and Sasol. She was also managing director and then president of the Black Management Forum (BMF). Over a career spanning 25 years, Nolitha spearheaded programmes that ensure the development of women and marginalised communities in the workplace and society. A passionate advocate for diversity and inclusion, she has earned a well-deserved reputation as a corporate activist. Nolitha is held in high regard within business circles and serves on numerous boards including the JSE Limited, Anglo American plc and Afrox Limited. Although Boardroom Dancing is her personal journey, it is also a lesson for South Africans committed to the transformation of boardrooms and the economy, and for women looking for role models as they climb corporate ladders and become thought-leaders."-- Back Cover.
Early years -- Growing up in a matriarchy -- Bethel college -- Finding my freedom -- Stepping out -- Liberations -- Embracing democracy -- Earning a place at the table -- A national stage -- Synergistic symphonies: the power of collaborations -- (Redefining) a woman's place -- Another kind of integration -- Preparing to fly -- Global transformation -- Awakening a South African giant -- Thinking globally, acting locally -- Extending my reach -- The journey ahead -- Reigniting the gender agenda -- We need to talk.
"Nolitha grew up as a shopkeeper's daughter in the Eastern Cape, studied at the University of Fort Hare and then entered the workplace in 1990 as a graduate trainee at Woolworths. Subsequently, she has worked in very senior positions at some major blue-chip companies, including Woolworths, Nedbank and Sasol. She was also managing director and then president of the Black Management Forum (BMF). Over a career spanning 25 years, Nolitha spearheaded programmes that ensure the development of women and marginalised communities in the workplace and society. A passionate advocate for diversity and inclusion, she has earned a well-deserved reputation as a corporate activist. Nolitha is held in high regard within business circles and serves on numerous boards including the JSE Limited, Anglo American plc and Afrox Limited. Although Boardroom Dancing is her personal journey, it is also a lesson for South Africans committed to the transformation of boardrooms and the economy, and for women looking for role models as they climb corporate ladders and become thought-leaders."--Back cover.
Includes bibliographical references.
Keywords: Fakude, Nolitha; Women executives -- South Africa -- Biography; Women in the professions -- South Africa -- Biography; International business enterprises -- Management